Contrastive Lexicology, Bilingual Lexicography and Translation - Z HAROUNI (Revue des Sciences Humaines, 2004)
This paper attempts to examine the intrinsic relationship between lexicology as a branch of linguistic study, lexicography or dictionary-making and translation which is, par excellence, an exercise involving micro and macro-linguistic features at an inter-lingual level. Through such an account, this paper aims to show, more particularly, the role of Lexicology as the science of lexis, i.e., the study of the various morphological and semantic processes by means of which the lexicon of a language is structured, in lexicography and the significant role they  both play in translation theory and practice. Therefore, lexicology and lexicography are considered here at the bilingual level resulting in contrastive lexicology and bilingual lexicography respectively